Quantum-classical correspondence and the role of the dipole function in molecular dissociation - Lima, Emanuel Fernandes de [UNESP]; Rosado, E. C.; Castelano, L. K.; Carvalho, Ricardo Egydio de [UNESP] (Elsevier B.V., 2014)
We consider the quantum and classical dissociation dynamics of heteronuclear diatomic molecules induced by infrared laser pulses. The field-molecule interaction is given by the product of the time-dependent electric field and the molecule permanent dipole. We investigate the influence of the dipole function in molecular dissociation. We show that the dissociation can be suppressed at certain external field frequencies for a nonlinear and finite-range dipole function. The correspondence between quantum and classical results is established by relating classical Fourier amplitudes to discrete-continuum quantum matrix elements. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Quantum-classical correspondence; Dipole function; Molecular dissociation; Morse oscillator